The Double Threshold: Consequences for Identifying Low-Dose Radiation Effects - Alan Waltar; Ludwig Feinendegen (SAGE Publishing, 2020)
Prior to observing low-dose-induced cell signaling and adaptive protection, radiogenic stochastic effects were assumed to be linearly related to absorbed dose. Now, abundant data prove the occurrence of radiogenic adaptive protection specifically at doses below ∼ 200 mGy (with some data suggesting such protection at a dose even higher than 200 mGy). Moreover, cells do not thrive properly when deprived of radiation below background dose. Two threshold doses need be considered in constructing a valid dose-response relationship. With doses beginning to rise from zero, cells increasingly escape radiation deprivation. The dose at which radiation-deprived cells begin to function homeostatically provides dose Threshold A . With further dose increase, adaptive protection becomes prominent and then largely disappears at acute doses above ∼ 200 mGy. The dose at which damage begins to override protection defines Threshold B . Thresholds A and B should be terms in modeling dose-response functions. Regarding whole-body responses, current data suggest for low-LET acute, non-chronic, irradiation a Threshold B of about 100 mGy prevails, except for leukemia and probably some other malignancies, and for chronic, low dose-rate irradiation where the Threshold B may well reach 1 Gy per year. A new Research and Development Program should determine individual Thresholds A and B for various radiogenic cell responses depending on radiation quality and target.